2018
DOI: 10.5812/jjm.69136
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Hepatitis C Virus Genotypes and Related Risk Factors Among Iranian Blood Donors: A Penalized Logistic Regression

Abstract: Background: The hepatitis C virus (HCV) is a blood born virus and the major cause of liver diseases worldwide. Distribution of HCV genotypes varies depending on geographical regions and routes of infection. Knowledge regarding the distribution of HCV genotypes and related risk factors plays an essential role in the control of HCV infection in the community. Objectives: The current study aimed at determining the current distribution of HCV genotypes and related risk factors among Iranian blood donors. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Some recently conducted studies reported changes in the distribution of HCV genotype as replacement of geno-type 3a, instead of genotype 1a, as the most common genotype among Iranian blood donors (13). In the presented study, the phylogenetic tree (Figure 1) revealed that genotype 3a sequences isolated from blood donors were not genetically different from that of IDUs, which is similar to the study conducted on blood donors in the Netherland (19).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Some recently conducted studies reported changes in the distribution of HCV genotype as replacement of geno-type 3a, instead of genotype 1a, as the most common genotype among Iranian blood donors (13). In the presented study, the phylogenetic tree (Figure 1) revealed that genotype 3a sequences isolated from blood donors were not genetically different from that of IDUs, which is similar to the study conducted on blood donors in the Netherland (19).…”
Section: Discussionsupporting
confidence: 85%
“…that genotype 1a is the most frequent subtype, followed by subtype 3a, in transfusion-related HCV infection patients (9,10), and genotype 3a is reported to be the most common genotype in IDUs and blood donors (11)(12)(13).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations